Cisplatin-based combination therapies: Their efficacy with a focus on ginsenosides co-administration - Li, Keke; Li, Jiwen; Li, Zhongyu; Men, Lei; Zuo, Haibin; Gong, Xiaojie (Pharmacological research, 2024)
Cisplatin, a frequently prescribed chemotherapeutic agent, serves as a clinically therapeutic strategy for a broad range of malignancies. Its primary mode of action centers around interference with DNA replication and RNA transcription, thereby inducing apoptosis in cancer cells. Nevertheless, the clinical utility of cisplatin is constrained by its severe adverse effects and the burgeoning problem of drug resistance. Ginsenosides, potent bioactive constituents derived from ginseng, possess an array of biological activities. Recent scientific investigations underscore the substantial amplification of cisplatin's anticancer potency and the mitigation of its harmful side effects when administered concomitantly with ginsenosides. This review aims to explore the underlying mechanisms at play in this combination therapy. Initially, we provide a concise introduction to the cisplatin. Then, we pivot towards illuminating how ginsenosides bolster the anticancer efficacy of cisplatin and counteract cisplatin resistance, culminating in enhanced therapeutic outcomes. Furthermore, we provide an extensive discussion on the reduction of cisplatin-induced toxicity in the kidneys, liver, gastrointestinal tract, nervous system, and ear, accompanied by immune-fortification with ginsenosides. The existing clinical combined use of cisplatin and ginsenosides is also discussed. We propose several recommendations to propel additional research into the mechanisms governing the synergistic use of ginsenosides and cisplatin, thereby furnishing invaluable insights and fostering advancement in combined modality therapy. [Display omitted]